Studying the Effect of Using Precise Geodetic Products from Various Data Centers on Precise Point Positioning Accuracy - القاموع, أديب; أحمد, محسن; غوسبودينوف, سلافيكو; كحيله, عمار (Latakia University Journal -Engineering Sciences Series, 2020)
Precise Point Positioning (PPP) is one of the latest measurement technologies that rely on Global Navigation Satellite Systems (GNSS). This technique requires entering all values of the "Precise Error Modeling Terms". These values are in digital files format, and the final files are called (Precise Geodetic Products). These precise geodetic products are provided by the International GNSS Service (IGS), but after 2017, access to those products was transferred to Global Data Centers, such as the European Space Agency (ESA), Center of Orbit Determination in Europe (COD), and Jet Propulsion Laboratory (JPL), and the International GNSS Service Organization (IGS) is now issuing its own version of those products. The research aims to study the variation in the (precision and accuracy) of the positioning values, by adopting the Precision Point Positioning Technology (PPP), using precise geodetic products from four different data centers (IGS / ESA / COD / JPL). A local experiment was conducted to study this variance in a relative and absolute way. The results of the precision test showed the advantage of using the precise geodetic products of the centers (COD / ESA) over the two other centers (IGS / JPL), and the relative precision of the positioning values reached the rank (1.5 cm) on the East component, and the rank (0.9 cm) On the North component. Otherwise, within Accuracy Test, the mean squared error of the positioning is "More Accurate" by adopting precise geodetic products from (IGS / JPL), than by (COD / ESA) centers, and the positioning 2D-RMS reaches the rank (7-11 cm) when using precise geodetic products from (IGS) and the rank (2-12 cm) when using precise geodetic products from (JPL).